The structure of prior knowledge - Jain, Pinky (2014)
The phenomenon of prior knowledge is deep rooted in the rhetoric of education. There is much discourse within pedagogy about its value and pivotal role in the formulation of new learning. However teachers are not able to use prior knowledge effectively as they do not have a working sense of it, but are using it intuitively and colloquially. While researchers provide a multitude of definitions of prior knowledge, no one has examined its elemental structure in a way that provides a model for teachers to use and support learning. This deficit is surprising as prior knowledge is a universally accepted pedagogical notion. The aim of this thesis is to fill the deficit and establish a structure of prior knowledge.